Transforming financial systems for sustainability: The role of green financing in social-environmental progress and economic resilience - Nouvan, Reggy (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Amid the challenges of climate change and the escalating global environmental crisis, the concept of a green economy has become crucial in achieving sustainable development. A green economy aims to generate economic value without harming the environment while improving social well-being. In this context, green finance plays a vital role in supporting investments in environmentally friendly projects and sustainable businesses. Green financing refers to funds allocated for projects and programs aimed at environmental protection and fostering sustainable economic growth. Method: This article explores research on green financing, including international observations on the challenges of environmental financing and proposed solutions for green finance. The challenges of environmental financing in Indonesia are also analysed from a legal perspective. Furthermore, this research aims to examine how the banking sector participates in supporting green project financing in Indonesia. Findings: Findings indicate that funding for green projects can significantly impact the environment, society, and climate change mitigation efforts. However, numerous issues remain, such as a lack of understanding regarding financing environmentally friendly projects, varying definitions of green financing, insufficient coordination in policy frameworks related to environmental financing, misaligned policies, and a lack of incentives for investors and financial institutions interested in climate change mitigation. The objective of green financing is to provide funding for projects or developments that balance economic, social, and environmental considerations. Conclusion: The Indonesian government has issued regulations on the implementation of sustainable finance for commercial banks to support green financing. These regulations are also applicable to financial service institutions, issuers, and publicly listed companies. The study's findings suggest that Bank Indonesia and the Financial Services Authority (OJK) have regulations that influence lending, credit, and investment policies. Indonesia's legal framework for environmentally friendly financing appears promising, supported by the collaborative efforts of the business sector and the government in advancing sustainable finance. Novelty/Originality of this Article: This study contributes a legal and institutional perspective on green financing in Indonesia by analyzing regulatory support and challenges, offering a distinctive national lens often underrepresented in global green finance literature.